A Comparative Study on the In Vivo and In Situ Degradability of Napier (Pennisetum purpureum), Guinea (Megathyrsus maximus), and Paspalum (Paspalum conjugatum) as Forage Grasess - Goyo, Mart John M.; Gacutan, Jr, Manuel D.; Galvez, Lorina A.; Come, Warren D. (Future Science / FSH-PH Publications, 2025)
This study evaluated the in vivo and in situ degradability of 3 local forage grasses: Napier sp., Guinea sp., and Paspalum sp. Three (3) rumen-cannulated cattle of similar age were used for the degradability assessments. The in vivo experiment followed a 3×3×3 Latin Square Design (LSD), while the in situ degradability study employed a 3×5 factorial in a randomized complete block design (RCBD). Dietary treatments consisted of A–Napier sp., B – Guinea sp., and C – Paspalum sp. In the in vivo digestibility trial, no differences were observed except for GE and NDF digestibility. As for the test diets, in vivo digestibility was comparable using local forages in the feed and nutrient digestibility assays (p>0.05). In contrast, no significant interactions were observed in the in situ ruminal degradability in feed, DMD, CPD, NDFD, and ADFD (p>0.05). However, main effects for Forage (factor A) showed a significant effect for both DMD (p<0.0028) and NDFD (p<0.0385). In addition, feed degradability was significant (p<0.0189). For the incubation time (Factor B), feed disappearance, DMD, and ADFD showed strong quadratic effects (p<0.0018, p<0.0001, and p<0.0095, respectively), suggesting that the breakdown process began rapidly but gradually slowed over time. In contrast, CPD and NDFD displayed a linear increase (p<0.0001).